Preparation and characterization of superparamagnetic Fe3O4-chitosan nanocomposites - Cuong, Nguyen Duc; Hoa, Tran Thai; Khieu, Dinh Quang; Tung, Truong Quy; Hieu, Nguyen Van (Vietnam Journal of Chemistry, 2014)
In this study, superparamagnetic nanocomposite Fe3O4-chitosan has been prepared by two step method. The Fe3O4 nanoparticles were prepared by a co-precipitation process and subsequently coated with chitosan. The magnetite nanoparticles and chitosan coated magnetic nanoparticles were characterized by XRD, IR and TEM. The magnetic properties were measured with homemade vibrating sample magnetometer (VSM) and evaluated in terms of saturation magnetization and coercivity. The results revealed that typical iron oxide nanoparticles were Fe3O4 with a core diameter of 15-20 nm. Magnetie nanoparticles were formed inside the chitosan matrix through possible binding of iron ions to NH2 group of chitosan. The Fe3O4-chitosan nanoparticles with core-shell structure exhibit superparamagnetic properties and highly dispersed nano magnetite particles with diameters around 15 nm. Keywords: Fe3O4, chitosan, superparamagnetic nanocomposite, two step method